Mediation as an Alternative to Legal Dispute Resolution in Health Services in Hospitals - Perangin-Angin, Thimothy Aryadi; Lamria Sintia Silaban; Sonya Airini Batubara; Jusnizar Sinaga (JUSTISI, 2025)
This research aims to analyze the role of mediation as a method of medical dispute resolution in Indonesia, which is seen as more effective, fair, and cost-effective than the litigation process. This research uses a normative legal method with a descriptive-analytical approach to identify legal principles, doctrines, and regulations related to medical dispute resolution. The main focus is dispute resolution through mediation in medical malpractice cases, which involves civil, criminal, and restorative justice aspects. The novelty of this research lies in the in-depth exploration of penal mediation as an approach in resolving criminal disputes related to medical malpractice, even though it does not yet have a strong legal foundation in the Indonesian criminal justice system. The results show that mediation, both in the civil and criminal realms, can provide a more humane and satisfying solution for all parties involved. However, the implementation of penal mediation still faces legal and practical challenges, especially in providing protection of patients' rights and ensuring justice for medical personnel.In conclusion, mediation has great potential in resolving medical disputes in Indonesia, but more specific regulations are needed to optimize its implementation, especially in criminal cases. As such, this study makes an important contribution to the development of a better medical dispute resolution mechanism in Indonesia.